Loretta P. Sweeny, where are youn - Giff, Patricia Reilly; Kramer, Anthony (New York Dell Publishing, 1983)
etermined crime-solver Abby finds a purple and orange wallet that she thinks may belong to a murderer.
Keywords: Mystery and detective stories